Peningkatan Pengetahuan Konsumsi Buah dan Sayur untuk Mencegah Anemia pada Remaja Putri SMA Negeri 11 Kota Jambi - Filius Chandra; Aisah Aisah (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Adolescent girls are a group that is vulnerable to nutritional deficiency problems. Nutrients in the blood can be determined through hemoglobin levels. Foods that are high in vitamin C and vitamin A are fruits and vegetables. In addition to vitamins, fruits and vegetables also contain fiber, folic acid, and various minerals. Sufficient recommendations for fruit and vegetable consumption according to the Balanced Nutrition Guidelines (2014) for toddlers, pre-school age (5-6 years) and school-age children (6-12 years) are 300-400 grams per day. Based on the initial survey conducted on students of SMA Negeri 11 Jambi City, which was conducted by interview, there were 8 out of 11 students who did not understand about nutritional problems in adolescents. The target community service activities are students of SMA NEGERI 11 Jambi City. The location of this community service implementation is at SMA NEGERI 11 Jambi City. Time of activity, the implementation of community service activities will be carried out in January 2022, with the aim of community service activities is to provide or add to the education of young women SMA NEGERI 11 Jambi City about consuming fruit and vegetables and nutritional problems in adolescents. When the pre-test and post-test were carried out regarding the knowledge of young women at SMA Negri 11 Jambi City before counseling was carried out about anemia, most of them had less knowledge as many as 19 people, 5 people had sufficient knowledge and 6 people had good knowledge, while the level of knowledge after counseling experienced an increase, namely respondents with a good level of knowledge as many as 20 people, enough knowledge as many as 7 people and less knowledge as many as 3 people.